2001
DOI: 10.1246/cl.2001.1014
|View full text |Cite
|
Sign up to set email alerts
|

The First Synthesis of Stilbene Dendrimers and their Photochemical trans–cis Isomerization

Abstract: Highly branched stilbene dendrimers underwent trans–cis isomerization in the excited singlet state within the lifetime of 10 ns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…From the time-resolved studies on energy and molecular volumes changes, it was found that the conformational change upon the trans-to cis-isomerization completed with the decay of the T 1 state for G0-G2. Photoisomerization in a series of stilbene dendrimers exhibiting fluorescence emission with considerably high quantum efficiencies was studied [107]. As shown in Ref.…”
Section: Stilbene Photoisomerization In Dendrimersmentioning
confidence: 99%
“…From the time-resolved studies on energy and molecular volumes changes, it was found that the conformational change upon the trans-to cis-isomerization completed with the decay of the T 1 state for G0-G2. Photoisomerization in a series of stilbene dendrimers exhibiting fluorescence emission with considerably high quantum efficiencies was studied [107]. As shown in Ref.…”
Section: Stilbene Photoisomerization In Dendrimersmentioning
confidence: 99%
“…In this area, the photoisomerization of dendrimers with photoresponsive cores-such as stilbene, [13][14][15][16][17][18][19][20][21] azobenzene, [22][23][24][25][26][27][28][29][30][31][32][33] diarylethene, [34][35][36][37][38] intramolecularly hydrogen-bonded chromophores, [39][40][41] and photolabile chromophores 42-44 -has been extensively investigated. We recently reported that stilbene dendrimers with benzyl ether-type dendrons exhibited a volume-conserving isomerization mechanism and a macromolecular effect (or generation effect) on energy transfer efficiency from the peripheral dendrons to the core stilbene in organic solvents [45][46][47] and aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…Among a number of photochemical molecular transformations, the E/Z-photoisomerization of olefinic compounds is the most fundamental and important process and this photochemical reaction in the confined environments has been extensively studied [1][2][3][4][5][6][7][8][9][10][11][12] in relation to the protein-bound visual chromophore. While the photoisomerization by conventional rotation, i. e., the 180 o rotation around the double bond, is regarded to be difficult within the narrow space such as in a crystal or solid-state, the Hula-twist (HT) mechanism, a space-conserving isomerization process, was proposed by Liu et al to explain such the phenomena [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…While the photoisomerization by conventional rotation, i. e., the 180 o rotation around the double bond, is regarded to be difficult within the narrow space such as in a crystal or solid-state, the Hula-twist (HT) mechanism, a space-conserving isomerization process, was proposed by Liu et al to explain such the phenomena [13][14][15][16][17]. Not only this hypothesis has sometimes been applied to the numerous examples of E/Z-photoisomerizations in the confined environments [7,[9][10][11][12], but also several investigations have been undertaken to verify this process [18][19][20][21][22]. However, only the 1,2-disubstituted ethylenes were employed in almost all examples previously reported, but, to the best of our knowledge, the tri-and tetra-substituted alkenes have not been used for this type of investigation.…”
Section: Introductionmentioning
confidence: 99%